2022
DOI: 10.3390/met12060979
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Asymmetrical Rolled Aluminum Alloy Sheets Using the Visco-Plastic Self-Consistent (VPSC) Method

Abstract: Asymmetric rolling is a forming process that has raised interest among researchers due to the significant improvements it introduces to the mechanical response of metals. The main objective of the present work is to perform a numerical study on asymmetrical rolled aluminum alloy sheets to identify and correlate the effect of the additional shear strain component on the material formability, tensile strength, and texture orientations development during multi-pass metal forming. Conventional (CR), asymmetric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Thus, Figure 8a indicates that the AR sheet texture is dominated by Cube and Goss texture components, as corroborated by the ODF and the ideal orientation representation in Figure 8d. These components have been associated with the recrystallization phenomena in Al alloys processed by rolling [24,39]. On the other hand, when the sheet was rolled symmetrically and asymmetrically, a similar overall behavior was observed, as shown in Figure 8b,c.…”
Section: Microstructure and Texturementioning
confidence: 58%
See 1 more Smart Citation
“…Thus, Figure 8a indicates that the AR sheet texture is dominated by Cube and Goss texture components, as corroborated by the ODF and the ideal orientation representation in Figure 8d. These components have been associated with the recrystallization phenomena in Al alloys processed by rolling [24,39]. On the other hand, when the sheet was rolled symmetrically and asymmetrically, a similar overall behavior was observed, as shown in Figure 8b,c.…”
Section: Microstructure and Texturementioning
confidence: 58%
“…For that reason, this model has earned the attention of many researchers around the globe. For example, Graça et al [24] studied the shear effect of the ASR process employing the VPSC model in an Al alloy. The authors demonstrated that ASR improved the mechanical properties and the plastic strain ratio.…”
Section: Introductionmentioning
confidence: 99%
“…This modeling approach considers each constituent grain as an inclusion embedded within a homogeneous viscoplastic medium [36]. The VPSC is able to capture the mechanical behavior and texture evolution of FCC crystals [37][38][39]. The detailed continuum mechanics and the homogenization method of the VPSC can be referred to in Appendix A.…”
Section: Vpsc-cdd Modelmentioning
confidence: 99%